The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.jcrs.2007.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Activity of superoxide dismutase isoenzymes in lens epithelial cells derived from different types of age-related cataract

Abstract: The level of TSOD, Cu/Zn-SOD, and Mn SOD isoenzyme activity decreased with age in LECs of patients with age-related cataract. A significant difference in the level of TSOD and Cu/Zn-SOD isoenzyme activity between different types of cataract was observed. The activity of all 3 SOD isoenzymes was highest in cortical cataracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Sorte et al [3] found that LEC DNA damage in cortical cataracts was significantly higher than that in nuclear and posterior subcapsular cataracts. Rajkumar et al [28] found the level of superoxide dismutase activity higher in the cortical cataract. However, most previous studies have also observed no difference in 8-HOdG, antioxidative enzymes and oxidative stress products in the three subtypes of ARC [4,5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Sorte et al [3] found that LEC DNA damage in cortical cataracts was significantly higher than that in nuclear and posterior subcapsular cataracts. Rajkumar et al [28] found the level of superoxide dismutase activity higher in the cortical cataract. However, most previous studies have also observed no difference in 8-HOdG, antioxidative enzymes and oxidative stress products in the three subtypes of ARC [4,5,29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epidemiological studies have indicated that apart from elevated intraocular pressure (IOP) and age, the risk of POAG might also be associated with ethnic origin, the presence of diabetes mellitus and most significantly, genetic predisposition [8,9,10]. In addition, oxidative stress is a very dangerous condition that can lead to the development of glaucoma, together with many other diseases [11,12]. Oxidative stress is defined as a shift in the pro-oxidant antioxidant balance in favor of the former caused by the production of inter alia reactive oxygen species (ROS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rajkumar et al demonstrated increased SOD activity in lens capsule samples from cortical cataract patients and the activity declined gradually with age in all samples; the highest levels of SOD were found in samples from patients 50 years of age or younger [20]. However, conflicting data on SOD activity levels also exist and there are studies showing decreased SOD activity levels in erythrocytes, sera and lenses from cataract patients compared to controls [2123].…”
Section: Discussionmentioning
confidence: 99%